Survey of freshwater fish in Kadamaian area, western Sabah - Soo, Chen Lin; Hairul Hafiz Mahsol; Simon Kuyun; Maxwell Kwang Sing Ginol; Azrie Alliamat; Nur Syafiqah Shamsul Kamal (Penerbit UMS, 2021)
The freshwater fish fauna was surveyed in forest streams located in the Kadamaian area, Sabah during the Borneo Geographic Expedition 2019. Fish samples were obtained from six stations by electrofishing from an upstream to downstream direction. A total of four families, 12 genera, and 14 species of fish were recorded from the present study. The most dominant family was Cyprinidae (10 species; 71.43%), followed by Gastromyzontidae (2 species; 14.29%), Nemacheilidae (1 species; 7.14%), and Mastacembelidae (1 species; 7.14%). The number of species was low in upstream stations at higher altitude but substantially higher in downstream stations with lower altitude. Economically valuable fish, Tor tambra was found at all stations. Gastromyzon monticola which is endemic to Sabah was also recorded at most stations.